Authority and Dynamics of Compliance to Resolve Sharia Digital Finance Disputes in Indonesia - Abdul Mujib (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This article focuses on analyzing the urgency of authorities in adapting technology to modern financial services. Conventional financial institutions (existing institutions) are entering a new era, where all financial transaction activities are connected to technology. The development of digital financial services such as electronic money (digital payments) and digital funds (crowdfunding) creates very fierce competition in today's modern financial services industry. The main problem that arises in the adaptation of information technology in financial services is legal certainty and protection for parties involved in digital financial transactions. This research analyzes the development trend of digital financial services in Indonesia. In addition, this study shows the efforts made by regulators in anticipating legal problems. Views on Islamic digital financial dispute resolution approaches and procedures are also the focus of discussion in this article. The method used in this study is literature research. This research uses an exploratory normative legal approach. Data collection techniques are carried out by observing, reviewing, and analyzing textual information which is then adapted as the main data in the discussion of this research topic. Data was collected from a literature review in the form of library materials or secondary data related to digital finance. This research produced several findings, namely: 1) the urgency of the authority in controlling the implementation of Islamic digital finance by presenting special regulations to minimize disputes between the parties. 2) Sharia digital financial platforms are ensured to have maximum Sharia compliance tools through Sharia compliance audits under the control of the authority.